Novas alternativas de remoção de enxofre do óleo diesel utilizando tensoativos e microemulsões - Duarte, Kahildete Rodrigues Forte (2014)
The diesel combustion form sulfur oxides that can be discharged into the atmosphere as particulates and primary pollutants, SO2and SO3, causing great damage to the environment and to human health. These products can be transformed into acids in the combustion chamber, causing damage to the engines. The worldwide concern with a clean and healthy environment has led to more restrictive laws and regulations regulating the emission levels of pollutants in the air, establishing sulfur levels increasingly low on fuels. The conventional methods for sulfur removal from diesel are expensive and do not produce a zero-level sulfur fuel. This work aims to develop new methods of removing sulfur from commercial diesel using surfactants and microemulsion systems. Its main purpose is to create new technologies and add economic viability to the process. First, a preliminary study using as extracting agent a Winsor I microemulsion system with dodecyl ammonium chloride (DDACl) and nonyl phenol ethoxylated (RNX95) as surfactant was performed to choose the surfactant. The RNX95 was chosen to be used as surfactant in microemulsioned systems for adsorbent surface modification and as an extracting agent in liquid-liquid extraction. Vermiculite was evaluated as adsorbent. The microemulsion systems applied for vermiculite surface modification were composed by RNX95 (surfactant), n-butanol (cosurfactant), n-hexane (oil phase), and different aqueous phases, including: distilled water (aqueous phase),20ppm CaCl2solution, and 1500ppm CaCl2solution. Batch and column adsorption tests were carried out to estimate the ability of vermiculite to adsorb sulfur from diesel. It was used in the experiments a commercial diesel fuel with 1,233ppm initial sulfur concentration. The batch experiments were performed according to a factorial design (23). Two experimental sets were accomplished: the first one applying 1:2 vermiculite to diesel ratio and the second one using 1:5 vermiculite to diesel ratio. It was evaluated the effects of temperature (25°C and 60°C), concentration of CaCl2in the aqueous phase (20ppm and 1500ppm), and vermiculite granule size (65 and 100 mesh). The experimental response was the ability of vermiculite to adsorb sulfur. The best results for both 1:5 and 1:2 ratios were obtained using 60°C, 1500ppm CaCl2solution, and 65 mesh. The best adsorption capacities for 1:5 ratio and for 1:2 ratio were 4.24 mg sulfur/g adsorbent and 2.87 mg sulfur/g adsorbent, respectively. It was verified that the most significant factor was the concentration of the CaCl2 solution. Liquid-liquid extraction experiments were performed in two and six steps using the same surfactant to diesel ratio. It was obtained 46.8% sulfur removal in two-step experiment and 73.15% in six-step one. An alternative study, for comparison purposes, was made using bentonite and diatomite asadsorbents. The batch experiments were done using microemulsion systems with the same aqueous phases evaluated in vermiculite study and also 20ppm and 1500 ppm BaCl2 solutions. For bentonite, the best adsorption capacity was 7.53mg sulfur/g adsorbent with distilled water as aqueous phase of the microemulsion system and for diatomite the best result was 17.04 mg sulfur/g adsorbent using a 20ppm CaCl2solution. The accomplishment of this study allowed us to conclude that, among the alternatives tested, the adsorption process using adsorbents modified by microemulsion systems was considered the best process for sulfur removal from diesel fuel. The optimization and scale upof the process constitutes a viable alternative to achieve the needs of the market